2021
DOI: 10.1098/rspb.2021.0070
|View full text |Cite
|
Sign up to set email alerts
|

The development of body representations: an associative learning account

Abstract: Representing one's own body is of fundamental importance to interact with our environment, yet little is known about how body representations develop. One account suggests that the ability to represent one's own body is present from birth and supports infants' ability to detect similarities between their own and others’ bodies. However, in recent years evidence has been accumulating for alternative accounts that emphasize the role of multisensory experience obtained through acting and interacting with our own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 100 publications
2
7
0
Order By: Relevance
“…As well as these findings on size, we found that in this paradigm the effects of visuotactile synchrony grew with age. Children therefore use multisensory information differently to adults in establishing ownership over a body part, supporting recent theories 42 that own-body representation develops over a prolonged developmental period, as a result of significant multisensory experience.…”
Section: Discussionsupporting
confidence: 77%
“…As well as these findings on size, we found that in this paradigm the effects of visuotactile synchrony grew with age. Children therefore use multisensory information differently to adults in establishing ownership over a body part, supporting recent theories 42 that own-body representation develops over a prolonged developmental period, as a result of significant multisensory experience.…”
Section: Discussionsupporting
confidence: 77%
“…This work suggests that somatotopy in S1 arises in part through 14 Hebbian processes that result in spatial correspondences between body parts and the representations of these body parts in somatosensory cortex. In turn, this line of thinking has guided a wider theoretical account of the development of body representations that relies heavily on associative processes (de Klerk et al, 2021). However, there are at least two reasons to sound a note of caution about this reliance.…”
Section: The Development Of Body Maps In the Infant Brainmentioning
confidence: 99%
“…Although we can label M. and A.’s behaviors as part of general diagnostic features of ASD, such as hyper/hypo-reactions to sensory stimuli and repetitive and restricted behaviors, it would be more informative to focus on the underlying neurocognitive processes and wonder about their consequences on each child’s sensory, motor, social, and cognitive development. For instance, both children seem to have atypical body representations, which can be defined as “the ability to integrate multisensory (visual, proprioceptive, and tactile) bodily information into coherent representations of one’s own body” [ 68 ] (p. 1). The basic processes underlying body perception are now known to be present from birth, with newborns preferring synchronous rather than asynchronous visuo-tactile stimulation only when the visual stimulus has the typical configuration of infant bodies [ 69 ].…”
Section: Practical Example: the Bodily Selfmentioning
confidence: 99%